Causative And Passive High Tone In Bantu: Spurious Or Proto? - Hyman, Harry (My University, 2022)
In this study I address Meeussen’s (1967: 92) tentative proposal to reconstruct a H tone on the Proto-Bantu causative *-i and passive *-ʊ suffixes, contrasting with all other Proto-Bantu extensions, which are reconstructed as toneless (Meeussen 1961; 1967). After surveying the phenomenon, I conclude that the causative-passive H (CPH) is almost exclusively limited to certain of the interlacustrine Bantu languages (JD40-60 and JE10-40) and should not be reconstructed. I exemplify the CPH tone effects in several of these languages and consider other cases of H tone extensions outside of the interlacustrine area which I argue to be unrelated. Although still requiring further investigation, I conclude by considering different morphological and phonological scenarios by which the CPH effects might have evolved.
Keywords: High Tone; Bantu; Spurious; Proto